Sosialisasi Tertib Administrasi Kependudukan Bagi Warga Pindah Datang Di Kelurahan Panjangjiwo - Kama Astrid Firdasari; Susi Hardjati (Jurnal Kabar Masyarakat, 2023)
This study aims to socialize about orderly population administration for residents who move in in Panjangjiwo Village, Surabaya City. This module aims to provide explanations and understanding to new residents regarding population administration rules and policies, so as to be able to create an aware and orderly society in population administration. awareness of the importance of population data. The method used in this socialization includes lecture sessions, discussions, and questions and answers. The resource person gave a detailed explanation of administrative rules to the participants. Participants also had the opportunity to discuss, share experiences, and ask questions related to population administration. Through this method, participants are expected to gain a comprehensive understanding. It is hoped that this socialization will be a guide for residents who move to the Panjangjiwo Village to understand and follow population administration rules and new residents can participate in creating a society that is aware and orderly in population administration.